Neuromuscular Fatigue in Unimanual Handgrip Does Not Completely Affect Simultaneous Bimanual Handgrip - Hikosaka, Mikito; Aramaki, Yu (Frontiers in Human Neuroscience, 2021)
Simultaneous bimanual movements are not merely the sum of two unimanual movements. Here, we considered the unimanual/bimanual motor system as comprising three components: unimanual-specific, bimanual-specific, and overlapping (mobilized during both unimanual and bimanual movements). If the force-generating system controlling the same limb differs between unimanual and bimanual movements, unimanual exercise would be expected to fatigue the unimanual-specific and overlapping parts in the force-generating system but not the bimanual-specific part. Therefore, we predicted that the decrease in bimanual force generation induced by unimanual neuromuscular fatigue would be smaller than the decrease in unimanual force generation. Sixteen healthy right-handed adults performed unimanual and bimanual maximal handgrip measurements before and after a submaximal fatiguing handgrip task. In the fatigue task, participants were instructed to maintain unimanual handgrip force at 50% of their maximal handgrip force until the time to task failure. Each participant performed this task in a left-hand fatigue (LF) condition and a right-hand fatigue (RF) condition, in a random order. Although the degree of neuromuscular fatigue was comparable in both conditions, as expected, the decrease in bimanual right handgrip force was significantly smaller than those during unimanual right performance in the RF condition, but not in the LF condition. These results indicate that for the right-hand, neuromuscular fatigue in unimanual handgrip does not completely affect simultaneous bimanual handgrip. Regarding the underlying mechanisms, we propose that although neuromuscular fatigue caused by unimanual handgrip reduces the motor output of unimanual-specific and overlapping parts in the force-generating system, when simultaneous bimanual handgrip is performed, the overlapping part (which is partially fatigued) and the bimanual-specific part (which is not yet fatigued) generate motor output, thus decreasing the force reduction.